2011
DOI: 10.1519/jsc.0b013e3181e8a4be
|View full text |Cite
|
Sign up to set email alerts
|

Training and Detraining Effects of the Resistance vs. Endurance Program on Body Composition, Body Size, and Physical Performance in Young Men

Abstract: The purpose of this study was to investigate the changes in the body composition, body size, muscle strength, and VO2max after 24 weeks of resistance or endurance training and detraining in young men. Thirty healthy college-aged men (20.4 ± 1.36 years) participated in the study. Subjects were assigned to resistance training group (RTG, n = 10), endurance training group (ETG, n = 10), and control group (CG, n = 10). The training program consisted of running or weight-resistance exercise for 3 sessions per week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 36 publications
3
21
0
5
Order By: Relevance
“…The detraining adaptations following strength or endurance training alone have been widely studied in different populations (8,9,26,31,36) Unfortunately, the effect of training cessation after CT has received less scientific attention (4,45,46,49). Moreover, although abrupt cessation of intense physical training is associated with a decline of physical performance (38-40), detraininginduced changes in performance after concurrent training are linked with multiple factors A C C E P T E D (16,31,36,46,49,50) among which is included the relative intensity used during previous resistance program. Therefore, the second aim of the present study was to analyze the effects of 4-week DT following concurrent training programs differing in load magnitude used during resistance training on different strength and aerobic parameters.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…The detraining adaptations following strength or endurance training alone have been widely studied in different populations (8,9,26,31,36) Unfortunately, the effect of training cessation after CT has received less scientific attention (4,45,46,49). Moreover, although abrupt cessation of intense physical training is associated with a decline of physical performance (38-40), detraininginduced changes in performance after concurrent training are linked with multiple factors A C C E P T E D (16,31,36,46,49,50) among which is included the relative intensity used during previous resistance program. Therefore, the second aim of the present study was to analyze the effects of 4-week DT following concurrent training programs differing in load magnitude used during resistance training on different strength and aerobic parameters.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Conversely, endurance training significantly changes body composition and promotes metabolic adaptations and maximum oxygen uptake, which leads to an increase in the training capacity. Although endurance training generally does not cause a significant muscle mass increase, it can be more effective than anaerobic resistance training in increasing maximal oxygen consumption (Lo, Lin, Yao & Ma, 2011). Toraman et al (2002) examined the effects of a 9-week training program on body composition in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Lo et al demonstrated that individuals who trained aerobically for a period of time and were subsequently maintained for 24 weeks without training (i.e., ''detrained'') lost the achieved adjustments with training and exhibited an increase in body weight and reductions in VO 2max [40]. Other studies [29,[41][42][43][44][45] have argued that detraining produced losses in aerobic capacity, altered body composition and decreased basal metabolism.…”
Section: Discussionmentioning
confidence: 99%